Laboratory Model Study on the Pile-Forming Mechanisms and Bearing Deformation Characteristics of CFA Piles. (10th December 2021) - Zhu, Deliang; Li, Yue; Zheng, Lingwei; Fang, Pengfei; Xie, Xinyu
Abstract : To study the pile-forming mechanism and bearing deformation characteristics of continuous flight auger (CFA) piles, a series of procedures, including helical drilling, pulling up/grouting, and inserting cage/pile forming, were simulated in clay-sand double-layer foundations by a homemade model drilling machine system in laboratory model tests. The effects of two different pile-forming methods on the load transfer and bearing characteristics of the piles were investigated by performing a model test comparison of CFA piles and bored piles. The experimental results show that there exist a soil improvement effect around the pile and a diameter expansion effect during the drilling process and grouting process for the CFA pile, which can effectively improve the lateral friction resistance of the pile. Compared with the bored pile, the pile diameter in the middle of the CFA pile increased by 19%, and the total lateral friction resistance of the CFA pile increased by 9.1% at a high load (1500 N). The comparative results of the model tests show that the bearing capacity of a single CFA pile increased by 50.0% and that the total settlement decreased by 40.5%. The results of the in situ test piles show that the load-settlement curves of the two pile types are similar under low-medium loads and that the lateral friction resistance of the CFA pile under high loads is better developed, which is relatively consistent with the model test results.